Petunidin alleviates diabetic nephropathy injury via the inhibition of oxidative stress and ferroptosis through the Keap1/mitoNQO1 pathway - Qiu, Yuli; Chen, Chao; Li, Xinyan; Chang, Yiling; Zou, Xiaoqin; Yan, Xiaopei; Mao, Wenjun; Wu, Gang; Li, Su; Chen, Yuqiong (Frontiers in Cell and Developmental Biology, 2025)
BackgroundDiabetic nephropathy (DN) is one of the most serious complications of diabetes and the leading cause of end-stage renal disease worldwide. The pathogenesis of DN is complex, and oxidative stress and ferroptosis play key roles. Petunidin (PET) is a member of the anthocyanin family and has strong antioxidant activity. However, there are no relevant studies on the use of PET to improve diabetic nephropathy. The aim of this study was to investigate the protective mechanism of PET in diabetic nephropathy.MethodsIn the animal experiments, db/m and db/db mice were treated with PET for 8 weeks. Renal function, urinary albumin/urinary creatinine ratio (ACR) and renal tissue section staining were used to observe renal pathological injury. For the cell experiments, normal renal cortex proximal convoluted tubule epithelial cells (HK-2 cells) were selected for further verification, and ADV-mediated Keap1 and mitoNQO1 overexpression models were constructed. Western blotting, immunofluorescence and TUNEL staining were used to detect oxidative stress- and ferroptosis pathway-related indicators.ResultsKeap1 expression in the kidneys of db/db mice was significantly increased, along with reduced mitochondrial translocation of NQO1, while PET reversed this trend to decrease oxidative stress and inhibit ferroptosis. Further experiments confirmed that after overexpression of Keap1, the protective effect of PET in high glucose-induced HK2 cells disappeared, whereas overexpression of mitoNQO1 reduced oxidative stress and ferroptosis in a mitochondria-dependent way.